A Multimodal Critical Discourse Analysis of Garnier Green Beauty Advertisement - Dang Arif Hartono; Stefanus Angga Badara Prima; Wisnu Sakti Dewobroto (ITScience (Information Technology and Science), 2022)
This study investigates how a multinational cosmetic company uses its advertising to promote green cosmetics in Indonesia. Using Multimodal Critical Discourse Analysis (MCDA), the study analyzes how Garnier utilized linguistics features and discourse strategies and positioned their customers in the Garnier Green Beauty advertisement. The analysis revealed that Garnier employed some linguistic features (e.g., positive adjectives, pronouns, repetitions, etc.) and scientific-sounding words as a discourse strategy in the advertisement. It was also found that Garnier made a deliberate marketing decision to employ advertising, positioning their customer as empowered actors to create socio-environmental change. The findings also discuss the features distinguishing green cosmetics advertisements from typical ones.